An Analysis of the Effects of Competence, Internal Locus of Control, and Work Culture on Employee Organizational Commitment: A Case Study at Kraton Regional General Hospital, Pekalongan Regency - Elsandra Novita Halim; Vip Paramarta; Etty Sofia Mariati Asnar (Eduvest - Journal of Universal Studies, 2026)
This study aims to analyze the effects of employee competence, internal locus of control, and work culture on organizational commitment at Kraton Regional General Hospital (Rumah Sakit Umum Daerah/RSUD Kraton), Pekalongan Regency, both partially and simultaneously. A quantitative approach with multiple linear regression analysis was employed. The study population comprised 232 employees of RSUD Kraton. Data were analyzed to measure the effect of each independent variable on organizational commitment. Internal locus of control was found to exert the most dominant influence on organizational commitment, with a regression coefficient (B) = 0.346, t = 11.097, p = 0.000. Employee competence also had a significant effect, with B = 0.245, t = 6.888, p = 0.000. Work culture, however, did not demonstrate a statistically significant effect, with B = 0.010, t = 0.246, p = 0.807 (p > 0.05). Simultaneously, the three variables jointly and significantly influenced organizational commitment. Among the predictors, internal locus of control emerged as the most dominant factor, followed by employee competence, both of which significantly affected organizational commitment. Competence was found to support the enhancement of employee engagement, whereas work culture, although positively directed, did not yield a statistically significant effect. These findings suggest that strengthening internal locus of control and developing employee competence are more effective strategies for enhancing organizational commitment at RSUD Kraton than improving work culture alone.